International Financial Statistics, February 2015. (International Financial Statistics; International Financial Statistics, 2015)
This monthly issue of International Financial Statistics (IFS) is a standard source of statistics on all aspects of international and domestic finance. Information is presented in tables for specific countries and in tables for area and world aggregates. Quarterly issues of this publication provide, for 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. In addition, similar summary tables for the world, industrial countries, and developing countries are included. The yearbook provides, for the most recent seven years, detailed trade data by country for approximately 184 countries, the world, and major areas. This annual publication provides detailed data on transactions in revenue, expense, net acquisition of assets and liabilities, other economic flows, and balances of assets and liabilities of general government and its subsectors. The data are compiled according to the framework of the 2001 Government Finance Statistics Manual, which provides for several summary measures of government fiscal performance. In IFS, exchange rates are expressed in time series of national currency units per SDR and national currency units per US dollar, or vice versa.